Social mobilisation, community engagement and the power of elites in rural development. Issue 2 (17th February 2021) - Khan, Shahzad; Short, Patricia
ABSTRACT: This paper presents an analysis of social mobilisation and community engagement in contexts where traditional relations of power are elite-based and exclusionary. Informed by contemporary critiques of community development, it takes the Pakistan-based Rural Support Programme Network's (RSPN) "three-tier social mobilisation strategy" as a case study and asks whether and how it has transformed traditional relations of power. The study reveals that despite a strategic focus upon transforming community relations and reducing social inequities, RSPN's specific mobilisation strategy, in practice, enables traditional elites to exploit newly formed community organisations in ways that reproduce traditional, exclusionary, elite-based relations of power.